Effect of gender differences on prevalence of asymptomatic bacteriuria - Milad, Hadel (faculty of applied basic medical science - Libyan international medical university, 2022)
Urinary tract infection (UTI) is a common bacterial illness that affects many sections of the urinary tract, and it can affect both men and women. Although both men and women are susceptible to the illness, women are more sensitive due to their anatomy and reproductive system. Bacterial invasion of the urinary tract, comprising the lower and upper urinary tract, is the most common cause of infection. Escherichia coli is the most common bacterial species, accounting for 80 to 85 percent of infections, followed by Staphylococcus species, which account for 10 to 15 percent. the bacterial species Klebsiella, Pseudomonas, Proteus, and Enterococcus have a limited role in the transmission of illness.
Keywords: Bacteriuria